Metafora Antropomorfis dalam Lirik Lagu “Kontras” karya Figura Renata - Atika Gusriani (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Multiple interpretations are understandings that arise in various ways as a result of song lyrics that are implied so that it is difficult to interpret a song that is heard. This study aims to describe the metaphor in the lyrics of the song “kontras” by Figura Renata, focusing on anthropomorphic metaphors. This research uses descriptive research method. The data contained in this study is qualitative data consisting of words, phrases, clauses, and sentences in the form of lexicon and lexical meaning in the lyrics of the song